The future of Indian universities : comparative and international perspectives - International Conference on 'The Future of Indian Universities: Comparative Perspectives on Higher Education Reforms for a Knowledge Society' (2013 : O. P. Jindal Global University); Kumar, C. Raj; O. P. Jindal Global University (New Delhi, India : Oxford University Press, 2017)
This volume emphasizes the need for fundamental reforms into the existing institutional structure of higher education and their governance so as to infuse much needed dynamism and renewed sense of purpose in the higher education sector in India. The contributors to the volume argue that universities ought to be dynamic institutions where new ideas are exchanged, mistakes made, and lessons learnt. The contributors highlight the fact that the university system in India is based upon a bureaucratic command and control system that constrains the freedom and liberty required for academic pursuit, and disallows flourishing of academic cultures in tandem with the changing demands of India's economy and democracy.
Section I : Indian universities : imaginations, aspirations, and expectations. The future of higher education in India / C. Raj Kumar -- An invitation to a thought experiment : quality, diversity, and the epistemics of university / Shiv Visvanathan -- The future of Indian universities : voices from within beckoning for the future / Indira J. Parikh -- The Indian university in a comparative perspective / N.R. Madhava Menon -- Strategic management of expansion of higher education in India : key policy interventions for change / Pawan Agarwal -- Building new institutions of excellence in India : three case studies of innovation / Pramath Raj Sinha -- Section II : Indian higher education in a comparative perspective : policy, regulation, and management. Future of Indian universities : need for a liberalized legal regime / A. Francis Julian -- Global competitiveness, privatization, dignified spaces, and curricular reform in Indian higher educaiton / Kanti Bajpai -- Challenges of knowledge creation for Indian universities / Stephen P. Marks -- Science-policy interfaces in an era of global commodification / Barbara Harriss-White -- Creating educational excellence : the role of culture at the Indian Institute of Management, Ahmedabad / Shailendra Raj Mehta -- Challenges of creating a world-class global private university in India : perspective of an administrator / Y.S.R. Murthy -- Deconstructing the discourse on university social responsibility / Anajika Srivastava -- Section III : Pedagogy of interdisciplinarity : law, humanities, and global studies in India. The phoenix of interdisciplinarity in higher education / Yugank Goyal -- The role of humanities in a university education / Alice Prochaska -- The liberal arts in the American context : what India can learn from Western liberal education / Carol M. Bresnahan -- Public policy as a practice : reflections inspired by Alasdair MacIntyre's After Virtue / R. Sudarshan -- Global studies in Indian universities : past imperfect, future circumspect / Sreeram Chaulia -- Clinical legal education and democracy in India / Sital Kalantry -- Appendix 1 : Sonipat Declaration -- Appendix 2 : President's speech.
""This volume was inspired by an International Conference on 'The Future of Indian Universities: Comparative Perspectives on Higher Education Reforms for a Knowledge Society' that was held on the campus of the O.P. Jindal Global University (JGU) in 2013""--Acknowledgements.
Includes bibliographical references (pages 438-451) and index.
Keywords: Education, Higher -- India -- Congresses; Higher education and state -- India -- Congresses; Universities and colleges -- India -- Congresses